2022
DOI: 10.31849/elsya.v4i1.8017
|View full text |Cite
|
Sign up to set email alerts
|

Hello English App for Online Learning during the Pandemic: Does it Enhance the Students’ English Vocabulary Development?

Abstract: The aims of the research were to examine the effect of Hello English application on students’ English vocabulary development at the seven-grade level of SMP PGRI Selapajang Jaya in academic year 2020/2021 and to know the perceptions of students on utilizing the Hello English App to increase English words. This study applied a quantitative method with quasi-experimental design. The seventh-grade students of SMP PGRI Selapajang Jaya in the academic year 2020/2021 was used as the population; also, the research sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This findings was supported by the study conducted by (Sudarmaji et al, 2022) who said that Hello English has a significance impact on the development of students" English words. Online applications are likely to result in effective assistance of learning and practicing both for language teachers/students and learning/teaching processes (Ipek & Ustunbas, 2021).…”
Section: Discussionsupporting
confidence: 58%
“…This findings was supported by the study conducted by (Sudarmaji et al, 2022) who said that Hello English has a significance impact on the development of students" English words. Online applications are likely to result in effective assistance of learning and practicing both for language teachers/students and learning/teaching processes (Ipek & Ustunbas, 2021).…”
Section: Discussionsupporting
confidence: 58%
“…It has been reported in some studies as beneficial in supporting students' language learning process as well as in affecting students' vocabulary mastery. Another related finding is from Sudarmaji et al (2022) who stated that Hello English smartphone application is appropriate to be implemented in English language learning. The finding also showed that the use of…”
Section: Discussionmentioning
confidence: 95%
“…Most students and teachers were forced to switch from offline to online learning due to the COVID-19 pandemic which had a significant impact on learning (Suherman et al, 2021;Sudarmaji et al, 2022). Every teacher must carry out online teaching, and be directed to use various digital tools and resources to solve problems and apply new approaches to learning (Eickelmann & Gerick, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…or offline (outside the network). Although it is unavoidable from the negative risks of using technology (Hendratno, 2022), the positive impact is also greater because the demands of technology for online learning are very much needed in the Covid-19 situation (Sudarmaji et al, 2022).…”
Section: Introductionmentioning
confidence: 99%